Functional and Quality-of-Life Outcomes of Pelvic Floor Physiotherapy Following Urological, Hip, and Perineal Surgeries - Sher Dil Khan; Hafiz Muhammad Atif; Usman Haider3 (Cuestiones de Fisioterapia, 2019)
Background: Pelvic floor dysfunction (PFD) has been identified as being under-appreciated in terms of being a potential post-surgical complication for various different operations. In this case, this analysis aimed at understanding post-surgical PFD in connection with urethroplasty, hemorrhoidectomy, and hip.Methods: The study enrolled 180 patients (60 patients per procedure) and followed them prospectively for a period of 12 months. The outcome assessment for the female pelvis was carried out by means of the Pelvic Floor Distress Inventory-20 (PFDI-20), surface electromyography, neurophysiology, and quantitative sensory testing. State-of-the-art modeling techniques such as machine learning and latent class analysis were used.Results: Baseline symptom burden had no significant differences between demographics (p=0.28). Both interventions resulted in an early postoperative boost in PFDI-20 scores that peaked between 6 and 8 weeks with partial recovery. Early pain intensity and hypertonus of the pelvic floor muscles predicted persistent dysfunction with good sensitivity and specificity of 0.88. Latent class analysis revealed four trans-procedural classes that distinguished between different intervention types: Neuropathic Phenotype, Pain Dominant Phenotype, Mechanical Phenotype, and Mixed Phenotype.Conclusion: Post-operative pelvic floor dysfunction is driven by shared mechanistic pathways rather than procedure alone. Phenotype-based assessment may enable targeted, interdisciplinary strategies to improve long-term functional outcomes.